Investigation of Some Properties of SnO2:Sb:F thin Films By an Economic Spray Pyrolysis Technique - Kocyigit, A.; Tatar D.; Battal A.; Aydin S.; Turgut G.; Duzgun B. (My University, 2013)
SnO2:Sb:F thin films deposited on glass substrate prepared by home-made spray pyrolysis method from low cost precursor SnCl2.2H2O and isopropyl solution. In this study, the effect of substrate-nozzle distance on physical, optical and electrical properties of film were investigated at 350 °C substrate temperature. The obtained results revealed that the structures and properties of the films were greatly affected at different substrate-nozzle distances. XRD patterns shown that all films crystalline in nature and preferred orientation are (200) plane and sometimes orthorhombic structures could be seen. The scanning electron microscope (SEM) images revealed that nearly all films are homogenous and smoothness. Uv measurement depicted that films are the best transmittance and the widest band gap for doubly doped SnO2 thin films from SnCl2 precursors in the literature 85 % and 4,33 eV respectively. Electrical study showed that the films are degenerate and exhibit n-type electrical conductivity. These films are useful as candidate for solar cell devices.
Keywords: Nanocrystals; Propanol solution; SnO2:Sb:F thin films; Spray pyrolysis; Substrate-nozzle distance